Perceived Aetiology and Therapeutic Attitudes: Mediating Role of Stigmatizing Attitudes in Substance Use Disorders - Sara Ishaq, Nashi Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Substance Use Disorders (SUDs) are among the most stigmatized mental health condition in Pakistan’s health care system. Stigma serves as a chief barrier to successful treatment engagement including seeking, sustaining participation or receiving quality care by health care professionals. Purpose: The present study aimed to investigate the mediating role of stigmatizing attitudes in explaining the relationship between perceived aetiology and therapeutic attitudes. Method: Correlational research design and purposive sampling strategy were used to collect a sample of 100 MHP’s (N= 100) consisting of n= 36 (M=33.64, SD=8.34) psychiatrists and n= 64 (M=30.38, SD=7.30) psychologist from hospitals, addiction centers and universities. Results: Results indicated that bio-medical causal attributions predicted stigmatizing attitudes (i.e., permissiveness, non-stereotype treatment optimism and treatment intervention); however, only treatment intervention mediated the relationship between bio- medical causal attributions and therapeutic preparedness among MHPs. Similarly, psychosocial causal attributions predicted stigmatizing attitudes (i.e., non-stereotype and non-moralism), however neither of them mediated the relationship between psycho- social causal attributions and therapeutic preparedness among MHPs. Conclusion: The study highlights the importance of combined aetiological information in anti-stigma interventions, advance training, and informed curriculum to reduce stigma and increase therapeutic preparedness. Keywords: Perceived Aetiology, Therapeutic Attitudes, Stigmatizing Attitudes, Substance Use Disorders